Attributable fractions for substance use in relation to crime. (31st March 2021) - Young, Matthew M.; De Moor, Chealsea; Kent, Pam; Stockwell, Tim; Sherk, Adam; Zhao, Jinhui; Sorge, Justin T.; Farrell MacDonald, Shanna; Weekes, John; Biggar, Emily; Maloney‐Hall, Bridget
Abstract: Aims: Building upon an existing methodology and conceptual framework for estimating the association between the use of substances and crime, we calculated attributable fractions that estimate the proportion of crimes explained by alcohol and six other categories of psychoactive substances. Design: Cross‐sectional surveys. Setting: Canadian federal correctional institutions. Participants: Canadian men ( n = 27 803) and women ( n = 1335) offenders who began serving a custodial sentence in a Canadian federal correctional institution between 2006 and 2016. Measurements: Offenders completed the computerized assessment of substance abuse, a self‐report tool designed to assess (1) whether the offence for which they were convicted would have occurred had they not been intoxicated from alcohol or another substance, (2) whether they committed the offence to support their alcohol or other substance use and (3) whether they were dependent on alcohol (alcohol dependence scale) or another substance (drug abuse screening test). Offences were grouped into four mutually exclusive categories: violent crimes, non‐violent crimes, impaired driving and substance‐defined crimes. This study focused on violent and non‐violent crime categories. Substances assessed were: alcohol, cannabis, opioids, other central nervous system (CNS) depressants, cocaine, other CNS stimulants and other substances. Findings: According to offender self‐report, 42% of all violent and non‐violent crime would probably not have occurred if the perpetrator had not been under the influence of, or seeking, alcohol or other substances. Between 2006 and 2016, 20% of violent crimes and 7% of non‐violent crimes in Canada were considered attributable to alcohol. In contrast, all other psychoactive substance categories combined were associated with 26% of all violent crime and 25% of non‐violent crime during the same time‐frame. Conclusions: Attributable fraction analyses show that more than 42% of Canadian crime resulting in a custodial sentence between 2006 and 2016 would probably not have occurred if the perpetrator had not been under the influence of or seeking alcohol or other drugs. Attributable fractions for alcohol and substance‐related crime are a potentially useful resource for estimating the impact of alcohol and other substances on crime.